Poisoned, potent, painted arrows as an index of San personhood - Snow, Larissa Marie (My University, 2021)
This thesis takes an ontological approach to southern African Later Stone Age rock art research and interpretation. Using modern Kalahari San ethnographies and myths, as well as the nineteenth Century Bleek and Lloyd Archive of /Xam oral narrative, the diverse beings that compromise the San world and peoples’ relationships to them are explored, with particular focus on how material objects facilitate these relations. Following Alfred Gell’s writings, the technological aspects of rock art production are investigated in order to demonstrate the action-oriented nature of paintings and how rock art served as an important physical manifestation of transient and transformative persons, both human and non-. Marking a break from hermeneutics, the notion of symbolic images is replaced with agentive art works whose materiality is infused with social significance. Following on from this, a ubiquitous object in San life and rock art is examined, revealing how seemingly mundane things can be significant, not in spite of, but because of the work they accomplish. For the San, poison arrows used to hunt large game animals were material objects par excellence; by procuring vital meat and potency they engendered inter-person and interpersonal relationships and were consequently instrumental in achieving full personhood. Poison arrows are examined in terms of how they cemented relations between spouses, affines and trading partners; how they were agentive and appropriate technology for interactions with game and rain animals; how anti-social figures deployed sickening arrows, and how the San held colonists, whose humanity was up for debate, in their sights. So salient are arrows, the San even conceived of their interior life force in this objectified form. This thesis makes a wider contribution towards understanding how personhood is constituted by and dispersed through objects and the central role of material things in enmeshing people with the vital elements of their environment.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2021